2007
DOI: 10.1016/j.meatsci.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and sex effects on carcass and meat quality of suckling kids protected by the PGI “Cabrito de Barroso”

Abstract: Carcass composition and meat quality traits were evaluated in 55 suckling kids (27 males and 28 females) from Serrana (S), Bravia (B) and Serrana · Bravia (S·B) crossbred genotypes. Kids were slaughtered at 8-11 kg of live weight according to ''Cabrito de Barroso-PGI'' specifications and carcasses' left sides were totally dissected. Dressing percentage (based on ELW) did not vary between genotypes and sexes. Genotype B carcasses have better conformation, expressed in higher compactness index and muscle/bone ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
61
6
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 53 publications
25
61
6
2
Order By: Relevance
“…The results presented in this study for muscle yield according to the breed group were similar to those verified by Santos et al (2007) and Ferreira (2010) researching on Serrana, Bravia and Serrana x Bravia and Anglo-Nubian, Boer x Anglo-Nubian and ¾ Boer x mixed breed goats, slaughtered between 8 and 11 kg and 20 and 25 kg of body weight, respectively.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results presented in this study for muscle yield according to the breed group were similar to those verified by Santos et al (2007) and Ferreira (2010) researching on Serrana, Bravia and Serrana x Bravia and Anglo-Nubian, Boer x Anglo-Nubian and ¾ Boer x mixed breed goats, slaughtered between 8 and 11 kg and 20 and 25 kg of body weight, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Bone and other tissues yields were not affected by the feeding system, breed group and by the interaction of these two sources of variation, agreeing with Grande et al (2003), Santos et al (2007) and Menezes (2008), respectively. On the other hand, differ from the results obtained by Emerson (2012), which found an influence of breed group and feeding system on bone yield for goats.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This variability offers opportunities to be explored in production systems of lambs. The influence of genotype on fatty acid composition has also been observed in goats (Santos et al 2007;Pen˜a et al 2011). Emphasise that the fatty acid composition is influenced not only by genetic factors but also by environmental factors such as diet and supplementation.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly Fisher et al (2000) reported lower carcass conformation and fatness scores in Welsh Mountain and Soay lambs indicating thinner muscle and less fat cover of these breeds than in the Suffolk. It was reported in several studies that by the improvement in carcass weight, an increase in carcass measurements and conformation indexes would also be expected (Díaz et al, 2002;Santos et al, 2007).…”
Section: Chilled Carcass Traits and Fat Colourmentioning
confidence: 97%